SOLID BATH SOAP DOSAGE FORMULATIONS OF THE ETHANOL EXTRACT OF FRESH FRUIT OF MORINDA (MORINDA CITRIFOLIA L.) - Yanna Rotua Sihombing; Aminah Syarifudin; Rinaldo Berutu (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2018)
Morinda plants grow widely throughout the Pasipic and are one of the most significant sources of traditional medicine among the Pacific island community. Morindas contain natural antioxidants for skin health and saponins in the manufacture of soap. Morindas also has potential as an antibacterial (Flavanoid). The purpose of this research is to formulate the ethanol extract of the fruit of morinda (Morinda citrifolia L.) fresh bath soap. Preparations to become solid. This research uses experimental methods. Morinda fruit is extracted by a process of maceration. Solid bath soap preparations inspection conducted this research is test the pH with a concentration of 2,5%, 3,5% and 4,5%. Ethanol extract of the fruit of morindas can be preparations soap formulations in bath with solid inspection results show pH, pH range between 8,5-10,1 show that the solid bath soaps are qualified solid bath soap. The result showed solid bath soap preparations from ethanol extract of the fruit of morinda (Morinda citrifolia L.) fresh with variations in defferent concentrations can be formulated in to a solid bath soap.